Improving the pedestrian-level wind comfort by lift-up factors of panel residence complex: Field-measurement and CFD simulation. (1st February 2023) - Zhang, Xiaotong; Gao, Yafeng; Tao, Qiuhua; Min, Yunran; Fan, Juntao
Abstract: High-rise buildings in modern cities can hinder airflow and cause a weak local wind condition that intensifies pedestrian-level thermal discomfort. The lift-up design has been recognized as an effective way to improve wind comfort at pedestrian height levels due to its wind amplification effect. However, previous research has focused mainly on isolated buildings, while the influences of lift-up factors and their interactions on the pedestrian-level wind comfort have not been studied comprehensively enough. Therefore, this study aims to investigate the effects of lift-up ratio and positions of lift-up design on the pedestrian-level wind environments around a residence complex by combining field measurement and Computational Fluid Dynamics (CFD) simulation. An array of 12 panel buildings located in Chongqing was selected to collect relevant environmental parameters, including the mean wind velocity ratio (MVR) for model validation. Different simulation scenarios were set to quantitatively analyze the wind condition improvement in both the lift-up layer and the target research area of the residence complex. Results show that the lift-up position at both ends or in the middle has the most significant effect—about 94.83% and 96.03%—on improving lift-up layer MVR. In addition, the target area MVR of the optimal condition is 36.35% higher than that of the basic condition and continues steady growth with the increasing lift-up ratio. Findings in this study provide scientific references for city planners to improve pedestrian-level wind comfort. Highlights: Integrated effects of lift-up parameters on wind environments are investigated. Lift-up positions at both ends or in the middle are optimal for the lift-up layer. Lift-up position in the middle is optimal for the overall residential complex. Law of wind amplification with lift-up ratio in each lift-up position is explored.